Legal Aspects and Implementation of an Effective and Fair House Lease Agreement - Muchammad Catur Rizky; Didit Darmawan; Sudjai (Jurnal Hukum Lex Generalis, 2024)
A house lease agreement is a legal relationship that often occurs in the community, but its implementation still faces many challenges. This study aims to analyze the implementation of such agreements from a normative juridical perspective, identify the main problems, and provide strategic recommendations to create fairer and more effective agreements. Using the literature study method, it is found that the imbalance of bargaining position, lack of clarity of rights and obligations, and lack of legal literacy are the main causes of disputes. Unharmonized regulations and the lack of efficient dispute resolution mechanisms exacerbate the situation. This study recommends drafting written agreements with balanced clauses, strengthening legal literacy, harmonizing regulations, and developing alternative dispute resolution mechanisms. This study is expected to provide practical and theoretical contributions in the management of house lease agreements that are more fair and responsive to the needs of the community.